2019
DOI: 10.1111/mec.15299
|View full text |Cite
|
Sign up to set email alerts
|

Climatic vulnerabilities and ecological preferences of soil invertebrates across biomes

Abstract: Unlike plants and vertebrates, the ecological preferences, and potential vulnerabilities of soil invertebrates to environmental change, remain poorly understood in terrestrial ecosystems globally. We conducted a cross‐biome survey including 83 locations across six continents to advance our understanding of the ecological preferences and vulnerabilities of the diversity of dominant and functionally important soil invertebrate taxa, including nematodes, arachnids and rotifers. The diversity of invertebrates was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 47 publications
5
40
0
Order By: Relevance
“…Soil biodiversity is a key driver maintaining and promoting multiple ecosystem functions [2,[11][12][13][14]. Considering the high functional redundancy of soil microorganisms [33], most studies have focused on soil microbial diversity [12][13][14][15], while ignoring other soil biota, e.g., protists and invertebrates, which are key components of soil food webs in belowground ecosystems [1,34,35]. In addition, evidence for the link between soil biodiversity and multiple ecosystem functions is lacking in human-dominated agricultural ecosystems, and the factors in uencing BEF relationships remain largely unknown in complex real-world ecosystems over large spatial scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil biodiversity is a key driver maintaining and promoting multiple ecosystem functions [2,[11][12][13][14]. Considering the high functional redundancy of soil microorganisms [33], most studies have focused on soil microbial diversity [12][13][14][15], while ignoring other soil biota, e.g., protists and invertebrates, which are key components of soil food webs in belowground ecosystems [1,34,35]. In addition, evidence for the link between soil biodiversity and multiple ecosystem functions is lacking in human-dominated agricultural ecosystems, and the factors in uencing BEF relationships remain largely unknown in complex real-world ecosystems over large spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…However, ecological network information is still essential for estimating potential species interrelationships within complex soil food webs, and, in turn, for revealing the in uence of soil food web complexity on biodiversity-driven ecosystem functioning [2]. Secondly, we highlighted the potential limitations of sequencing approaches for the quantifying of soil invertebrate biodiversity; larger soil organisms would be potentially underrepresented based on such an approach, although a few studies have applied the approach to estimate the soil invertebrate biodiversity [2,3,34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, any global biodiversity monitoring should be initiated in a way that reduces spatial gaps in sampling (Cameron et al, 2018), using general calls for participation and/or more targeted communication. Bastida et al (2020) use molecular methods that are common in microbial studies, and going forward it is likely that molecular methods will increasingly be used for soil invertebrate sampling, especially in relation to such global monitoring. There are a number of advantages to validating such data.…”
Section: Introductionmentioning
confidence: 99%
“…While the biogeography of aboveground organisms has been the basis for fundamental rules in ecology and has helped inform decision makers about priority conservation habitats for decades, the global distribution of soil biodiversity has only recently seen a surge of scientific interest and synthesis work (Cameron et al, 2018). In this issue of Molecular Ecology, Bastida et al (2020) publish the first global maps of soil invertebrates that were sampled at 83 locations, across six continents, using standardised methods and DNA sequencing. This follows previous global maps on soil microbes (e.g., Delgado-Baquerizo et al, 2018;Tedersoo et al, 2014) and fauna (Phillips et al, 2019;van den Hoogen et al, 2019), as well as soil microbial and animal biomass (e.g., Fierer, Strickland, Liptzin, Bradford, & Cleveland, 2009).…”
mentioning
confidence: 99%
“…To date, the roles of abiotic drivers (e.g., pH, temperature, and nutrient content) in shaping the diversity and distribution of bacterial and fungal communities in terrestrial ecosystems have been well studied across regional to global scales [12][13][14]. Recent studies reported that the global distribution of soil faunal communities including earthworms, nematodes, and invertebrates, is primarily driven by vegetation and climate across many biomes [15][16][17]. However, biotic factors (e.g., soil faunal colony and activities) as a driving force of the diversity and assembly process of soil microbial communities remain largely unexplored at large spatial scales.…”
Section: Introductionmentioning
confidence: 99%